Comparison of Design and Cost of Reinforced Concrete Structures in Buildings with Brick, Brick and Light Brick Walls in front of SD No. 9 Benoa - Astariani, Ni Kadek; Sudika, I Gusti Made; Triatmaja, Putu Arif Prabawa (Universitas Ibn Khaldun Bogor, 2025)
In building structures, the accepted dead load is the load of the elements in the building, including reinforced concrete, rebated concrete, specs, ceramics, tiles, ceilings, MEP, walls and others. The wall load depends on what material is used on the wall. Bricks with half masonry provide a load of 250 kg/m2 (PPIUG, 1983). A pair of hollow brick walls weighs 120 kg/m2 (PPIUG, 1983) for HB 10. Light brick is concrete where air bubbles are caused by chemical reactions, AAC (Autoclaved Aerated Concrete) mixture generally consists of quartz sand, cement, lime, a little gypsum, water, and aluminum paste as a developer. Has a weight of 60 kg/m2 for the type with a thickness of 10 cm. Research is needed to compare the calculation results and structural costs of sloofs, beams, columns, ring beams and foundations in structures that use brick walls, concrete blocks and lightweight bricks. In this research, three structural models were created, namely those using brick walls, concrete blocks and lightweight bricks. Analysis was assisted using the SAP2000 Version 14.2.2 computer program. which refers to SNI-1726-2012 and SNI-2847-2013. In this research, a three-story school building located in Benoa, South Kuta Badung was studied. The results of the analysis resulted in a comparison of material requirements for the structural model with brick walls: In the overall structure, it was found that the concrete requirement in the model with brick walls was 15.71% smaller, while in the model with lightweight bricks it was 16.50% smaller. And the iron requirement for the model with bricks is 5.85% smaller, while for the model with lightweight bricks it is 6.69% smaller. The comparison of structural costs to the structural model with brick walls was found to be 8.67% smaller for the model with brick walls, and 9.26% smaller for the model with lightweight brick walls.